A Multi-Center, Randomized, Blind, Controlled Clinical Trial of the Safety and Efficacy of Micro Radio Frequency Therapy System for the Treatment of Overactive Bladder - Xu, Zhi-Hui; Zhang, Peng-Fei; Wang, Yu-Feng; Ma, Ao; Bano, Yasmeen; Ibrohimov, Alisherjon; Zhang, Chen; Jiang, Hao-Fei; Zhang, Yang; Yu, Yan-Lan; Jiang, Hai-Hong (Frontiers in Medicine, 2022)
Purpose The purpose of this study was to evaluate the efficacy and safety of low power micro radiofrequency (RF) therapy (μRFthera®) through urethra in the treatment of overactive bladders (OAB) through a prospective, single-blind, placebo-controlled, multi-center clinical protocol. Materials and Methods One hundred and fourteen patients with refractory OAB were randomized at 2:1 ratio, treatment to control undergoing same procedures except only the micro-RF treatment group at turned “on” setting in energy. Bladder diaries recorded during the screening period (3 days before enrollment) and during follow-up period on week 1, 3, and 7, respectively. The patients in control could choose receiving an energized treatment during extension stage. Results The treatment efficacy was 76.1%. There was 49.80% rate improvement compared to control (95%CL 32.48%, 67.13%). The crude rate ration (RR) was 2.89, 95% CI (1.67–5.01) with p < 0.001 in uni-variate analysis, while the RR became 2.94, 95% CI (1.67–5.16) with p < 0.001 after adjusted potential confounding factors in multi-variate analysis. Statistically significant improvements have been demonstrated in the frequency of urination, urgency, nocturia, and quality of life (QoL) scores. Conclusions Micro RF therapy is safe and effective for the treatment of OAB. The main treatment-related complications were catheterization related complications. Clinical Trial Registration Zhejiang Device Registration Certificate No. 202090909, www.chictr.org.cn, Clinical Trial Accession Number: ChiCTR2100050096.